Zimbabwe: Essays, Non Fictions and Letters - Mwanaka, Tendai R. (Book collections on Project MUSE., 2022)
Tendai Rinos Mwanaka wrote letters to Robert Mugabe, Constantine Chiwenga, Morgan Tsvangirai, The Zimbabweans, Emerson Mnangagwa, Nelson Chamisa, The Police, and in between infused the letters with deeply literary and psychoanalytic essays on the motivations of political players in Zimbabwe. Using this nonfiction literary form, the letter writing form, to protest against Robert Mugabe and the Mugabeism the letters were initially written to protest against Mugabe's continuing clinging to power, the collection has been expanded to include other issues related to Zimbabwe society. As the country moves towards a better multiparty democracy if there is change in thinking in these very important facets shaping Zimbabwe such as constitutionalism and rule of law, change and devolution of government, developmental agenda, and freedom of expression and association.